After the Korean War an intimate history - Gwon, Heon ig 1962- (Studies in the social and cultural history of modern warfare, 2020)
Following his prizewinning studies of the Vietnam War, renowned anthropologist Heonik Kwon presents this ground-breaking study of the Korean War's enduring legacies seen through the realm of intimate human experience. Kwon boldly reclaims kinship as a vital category in historical and political enquiry and probes the grey zone between the modern and the traditional (and between the civil and the social) in the lived reality of Korea's civil war and the Cold War more broadly. With captivating historical detail and innovative conceptual frames, Kwon's moving, creative analysis provides fresh insights into the Korean conflict, civil war and reconciliation, history and memory and critical political theory